Corruption and International Human Rights Law - Burneo Labrín, José (2009)
A first reading of the anti-corruption treaties in force shows that they do not establish any direct relationship with human rights. This situation is replicated with the treaties that deal with human rights in the international legal system, since there is no palpable link between them and corruption. In this context, the purpose of this study is to find the relationship between corruption and human rights from an international legal perspective. Although there is no ostensible link between the aforementioned concepts, the author argues that the fight against and prevention of corruption has its origin in the United Nations Charter and regional charters, since acts of corruption are contrary to the principles of those charters. To that extent, corruption represents a threat, affectation and hindrance to human rights and, in certain cases, represents a violation of those rights.